Single cell transcriptomic profiling of tau pathophysiology in a novel 3D neural‐glial coculture model. (1st February 2022) - Rickner, Hannah; Jiang, Lulu; Hong, Rui; Wolozin, Benjamin; Cheng, Christine
Abstract: Background: Research into neurodegeneration has been hampered by a lack of systems that rapidly and accurately recapitulate neurodegenerative processes. We report development of AstAD, a model combining human iPSC derived neurons (hiNCs) and astrocytes (hiACs) in self‐aggregating 3D organoids that reproducibly develop a robust range of tau pathology and neurodegeneration. AstAD is a scalable and highly manipulatable model of neurodegeneration and critical understudied glial responses. Additionally, the AstAD model induces pathology without reliance on genetic overexpression. AstAD represents an important technological advance in modeling Alzheimer's Disease (AD), and is a promising tool for identifying disease modifying treatments. Methods: The AstAD system was developed by combining advances in 3D cell modeling and tau propagation. We perform directed differentiation of wild‐type iPSC to hiNCs and hiACs, and hiNCs are selectively exposed to toxic aggregations to induce pathology. Cells are combined in microwells to induce self‐aggregation, and pathology develops over the course of three weeks. Tau pathogenesis in the AstAD model was correlated with human tauopathy progression by immunopathology and single cell transcriptomics, and the application of a selective inhibitor PU‐H71 demonstrated the efficacy of the model to explore disease modifying treatment. Result: The AstAD model consistently displays a robust range of tau pathology within three weeks, including progressive development of hyperphosphorylated tau at positions T181, S262, and S396/404, misfolded tau (MC1, TOMA2), and fibrillar tau (THIOS). Neurodegeneration (FlouroJadeB, LDH) is accompanied by reactive astrogliosis (GFAP), which single cell transcriptomics reveals to be driven by heat shock proteins (HSPs). The observed tau pathology and transcriptional responses were reduced by treatment with PU‐H71, which eliminates dysfunctional HSP epichaperome. Together this evidence demonstrates a rapid and reversible recapitulation of tau pathogenesis. Conclusion: The novel AstAD model consistently recapitulates tau‐induced neurodegeneration in a human system, and allows for the elucidation of neuronal and astrocytic responses. Additionally, we have demonstrated the power of AstAD to model the reduction of tau pathology by drug treatment. Continued expansion of the AstAD model will include integration of microglia. The AstAD model represents a technological advance that will allow for the rapid recapitulation of neurodegeneration in a manipulatable system that promises to accelerate drug development for AD.